EFFECTIVENESS OF DATES AND ACUPRESSUR ON PRODUCTION OF BREAST MILK IN CLINIC TAMAN SARI 2 PEKANBARU - Vitriani, Okta; Alyensi, Fatiyani; Susanti, Ari (JURNAL IBU DAN ANAK, 2021)
Breast milk is the most important nutrient for newborns. Breastfeeding improves the quality of life for both infants and mothers, as well as having an impact on children's growth and development. Only about 38% of the world's population is exclusively breastfed, and Indonesia ranks third lowest out of 51 countries. Breastfeeding failure is caused by the belief that breast milk is insufficient or has not come out in the initial days. The goal of this study was to see how effective dates and acupressure were at increasing breast milk production. A quasi-experimental research design with a two-group post-test design was used in this study. In 2021, the research was carried out in Pekanbaru's Taman Sari 2 Primary Clinic. Purposive sampling was used to collect the sample. The independent t-test was utilized for bivariate analysis. The average increase in breast milk production with acupressure was 0.290 (SD =.5763) and the given dates were 1,430 (SD = 1.3655), according to the findings. In postpartum women, dates were more successful in raising breast milk supply (p=0.031). Acupressure and dates can help postpartum women produce more breast milk. This is one of the recommendations for postpartum mothers who want to enhance their milk production.